Comparison of microbial community diversity in the manual work and mechanized production process of sauce-flavor high-temperature Daqu - TANG Shaopei, ZHU Guojun, WANG Zhenlin, LI Tingting, WANG Yi, ZHU Xia, WANG Xiaodan, ZHANG Liang, ZHAO Jinsong (Zhongguo niangzao)
The composition and difference of microorganisms in the production process of sauce-flavor (Jiangxiangxing) high-temperature Daqu in the manual workshop, the new and the old machine workshop were analyzed by high-throughput sequencing technology. The results showed that the composition of dominant microbial genera in Daqu was same whether the Daqu was produced manually or mechanically, the difference was mainly reflected in the relative abundance of each microbial genus. The dominant bacterial genera in the fermentation process of sauce-flavor high-temperature Daqu were Kroppenstedtia, Virgibacillus, Bacillus, Weissella, Scopulibacillus, Oceanobacillus, Saccharopolyspora, Pantoea and Limosilactobacillus, the dominant bacterial genera during storage were Kroppenstedtia and Virgibacillus. The dominant fungal genera in the fermentation process were Thermoascus, Thermomyces, Paecilomyces, Alternaria and Monascus, and the dominant fungal genera during storage were Thermoascus, Thermomyces and Paecilomyces. To sum up, the manual and mechanical production Daqu had a high similarity on the microbial level.